PENERAPAN KLAUSULA EKSONERASI DALAM PERJANJIAN BAKU PENGANGKUTAN BARANG MELALUI PERUSAHAAN ANGKUTAN DARAT CV AISON EXPRESS DI KOTA PEKANBARU - M. Wahyu Nugraha; Firdaus Firdaus; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Agreement is the main thing before carrying out cooperation, because the parties have made an agreement. in the clause of the article VIII expedition agreement paragraph 1 that if there is a claim for loss or damage to the shipment, the Carrier will settle the claim in accordance with the Guidelines for Procedures and Carrier Shipping Conditions, namely a reimbursement of a maximum of 5 (five) times the cost of sending specifically for items sent just lost or damaged.This type of research is sociological legal research, research that wants to see the correlation between law and society, so that it can reveal the effectiveness of the law in society and identify unwritten laws that apply to the community, this research in the Office of CV. Aison Express and RG Fried Chicken Pekanbaru, while the population and sample are all parts related to this study, data sources used among other things, primary data, secondary data and tertiary data, data collection techniques with interviews and literature.From the results of research and discussion it can be concluded that, first, the application of the exoneration clause in the standard contract for the transportation of goods and services by CV Aison Express can be concluded that there is a discrepancy between the application of the standard clause in a standard agreement with the rules governing it, as stated in Article 18 of Law Number 8 of 1999 concerning Consumer Protection. The clauses in the standard contract for the carriage of goods and services made by CV Aison Express staff do not refer to the applicable rules but only follow agreements that have been used by other expeditions without reviewing each clause so that there is an exoneration clause in the agreement. So as not to achieve the objectives of the formulation of the standard agreement. Second, legal liability as a form of responsibility for the implementation of exoneration clauses in the transportation of goods and services agreement by CV Aison Express can be concluded that the realization of CV Aison Express's willingness not to bear the cost of losses incurred by the application of exoneration clauses that are not in accordance with applicable regulations. Not finding good faith CV Aison Express to give responsibility as a form of awareness of having made a mistake.Keywords: Implementation, Standard Agreement, Carrier.